Freeze-dried Amorphous Dispersions for Solubility Enhancement of Thermosensitive API Having Low Molecular Lipophilicity - Kulthe, V. V.; Chaudhari, P. D.; Aboul-Enein, H. Y. (Drug Research, 2014)
The present study focuses on the development of an alternative ‘thermally gentle’ strategy such as freeze-drying to obtain not only solubility enhanced but also physically stabilised amorphous solid dispersions of acetazolamide, which melt with decomposition (M.P.~260°C). The solid dispersions were prepared by freeze-drying an aqueous dispersion of acetazolamide containing a lyoprotectant as sugar alcohol (mannitol) in 1:0.5, 1:1 and 1:2 proportions by weight. All the proportions of solid dispersions reported a marked increase in solubility characteristics compared to those of pure drug; with outstanding performance by 1:1 ratio of about 6 folds rise in saturation solubility and 90% drug release in about initial 30 minutes. This could be attributed to the formation amorphous molecular dispersions, cosolvent effect of mannitol on dispersed acetazolamide as well as its local solubilisation effect at the diffusion layer. During stability study also, 1:1 ratio of solid dispersions reported an insignificant change in solubility characteristics subjected to an unchanged amorphous nature. Such physical stability could be attributed to decreased molecular mobility of the drug molecules in amorphous carrier because of weaker drug-carrier interactions. Thus, it was demonstrated that freeze-drying is an effective method of forming dissolution-enhanced, amorphous solid dispersions of thermally degradable APIs.
Keywords: solvent sublimation; acetazolamide; strong crystal lattice; melts with decomposition; accelerated stability study